PEMBINAAN TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN KLAS IIA DENPASAR - Ardian Paramandika, I Gede; Mertha, I Ketut; Swardhana, Gede Made (Kertha Wicara : Journal Ilmu Hukum, 2014)
Implementation Guidance inmates in Denpasar Penitentiary Class IIA aims to determine how the implementation of coaching prisoners in Denpasar Penitentiary Class IIA and determine the factors that become resistor in the process of implementing coaching Inmates in Prison Class IIA Denpasar. The results showed that the implementation of coaching Narapiadana in Denpasar Penitentiary Class IIA through future stages of the introduction of the environment, followed by the formation of religious awareness, legal awareness, intellectual, spiritual physical health coaching, and skill-building work has not been done to the fullest. Factors affecting the implementation of coaching prisoners in Denpasar Penitentiary Class IIA include lack of infrastructure, insufficient number of security officers, the number of prisoners who exceed prison capacity limited number of teachers, as well as a lack of interest in prisoners.
Keywords: Penitentiary, Prisoners, Development